1989
DOI: 10.1017/s0022149x00009226
|View full text |Cite
|
Sign up to set email alerts
|

Further studies on the effect of cyclosporin A on the course of Paragonimus infection in rats

Abstract: Paragonimus ohirai-infected rats were treated with cyclosporin A (CyA) at different times during the course of infection. CyA (5×80 mg/kg) affected the worm recovery, growth and maturation rates of P. ohirai with respect to control values. This tendency was most remarkable in animals treated 15 days and more after infection with CyA (groups B, +15 to +19 days; C, +25 to +29; D, +35 to +39 and E, +45 to +49). In group A (0 to +4), however, the drug did not affect markedly the growth and maturation of worms, alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1990
1990
1999
1999

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…An unusual feature of this compound is its broad spectrum antiparasitic activity. CsA-treated mice, for example, are protected against Plasmodium berghei, P. chabaudi or P. yoellii infections (Nickell, Scheibel & Cole, 1982;Thommen-Scott, 1981), while CsA-treatment of rats and Mastomys natalensis confers significant protection against Paragonimus miyazakii and two filarial species respectively (Hashiguchi & Okamura, 1988;Bout, Haque & Capron, 19846;Zahner & Schultheiss, 1987). Features of the anti-schistosomal activity of CsA include reduction in worm burden (Bout, Deslee & Capron, 1984a, 1986Chappell et al 1987;Smith et al 1988), reduction in female worm fecundity (Nilsson et al 1985) and a reduction in the activity of a schistosome-associated haemoglobinase enzyme (Bueding, Hawkins & Cha, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…An unusual feature of this compound is its broad spectrum antiparasitic activity. CsA-treated mice, for example, are protected against Plasmodium berghei, P. chabaudi or P. yoellii infections (Nickell, Scheibel & Cole, 1982;Thommen-Scott, 1981), while CsA-treatment of rats and Mastomys natalensis confers significant protection against Paragonimus miyazakii and two filarial species respectively (Hashiguchi & Okamura, 1988;Bout, Haque & Capron, 19846;Zahner & Schultheiss, 1987). Features of the anti-schistosomal activity of CsA include reduction in worm burden (Bout, Deslee & Capron, 1984a, 1986Chappell et al 1987;Smith et al 1988), reduction in female worm fecundity (Nilsson et al 1985) and a reduction in the activity of a schistosome-associated haemoglobinase enzyme (Bueding, Hawkins & Cha, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Unpublished data show that the drug exerts powerful but selective action against juvenile Fasciola hepatica in rats and in vitro (Penlington et al in preparation). The effects of CsA on Paragonimus miyazakii and P. ohirai in rats vary according to treatment regime (see below) (Hashiguchi & Okamura, 1988. These and other models require further exploration to determine whether CsA is generally toxic to trematodes or whether its activity range is rather more narrow.…”
Section: Anthelmintic Activitymentioning
confidence: 99%
“…The effects of CsA on Paragonimus miyazakii in rats are dependent upon timing of drug administration relative to infection age. Treatment around time of infection results in increased worm growth and accelerated maturation while later drug treatment (at 15-19 days post-infection) brings about decreased recoveries of worms and reduced cyst formation in the lungs (Hashiguchi & Okamura, 1988). In the case of the related parasite, P. ohirai in rats (Hashiguchi & Okamura, 1989), CsA is exclusively anthelmintic regardless of time of treatment.…”
Section: Combined Immunomodulatory and Antiparasitic Activity Of Csamentioning
confidence: 99%
“…In addition to its immunosuppressive activities, CsA is also reported to exhibit anti-parasitic activity; these effects have been shown in a variety of host-parasite experimental systems. The anti-malarial activity of CsA has been demonstrated in mice infected with Plasmodium berghei, P. chabaudi or P. yoelii (Nickell, Scheibel & Cole, 1982;Thommen-Scott, 1981), while CsA-treated Mastomys and rats, show significant protection against filariae and Paragonimus respectively (Bout, Haque & Capron, 19846;Zahner & Schultheiss, 1987;Hashiguchi & Okamura, 1988). Several groups have shown that treatment of mice with CsA results in both immediate and prophylactic effects against Schistosoma mansoni infection (Bout, Deslee & Capron, 1984a, 1986Bueding, Hawkins & Cha, 1981;Nilsson et al 1985;Chappell et al 1987;Smith et al 1988), and that the anti-parasitic effects are not linked to the immunosuppressive activity of the drug.…”
Section: Introductionmentioning
confidence: 99%